Effectiveness of a comprehensive blood pressure control program in primary health care in Peru - Jong Koo Kim; Hye-yeon Jo; Miguel A. Malo; Eun Woo Nam (Pan American Health Organization, 2020)
Objective. To assess the effectiveness of a comprehensive blood pressure (BP) control program on improving lifestyle indicators, BP levels, and laboratory examination results among people living in low-income urban areas of Peru. Methods. A prospective before-and-after study design was applied to 1 271 participants with hypertension or pre-hypertension. The intervention was implemented for 2 years, from May 2015 - April 2017, in three health centers in Lima (2 in Comas and 1 in Callao). The changes in participants over the study period were compared. All participants were provided with individualized consultations, group health education sessions, regular group meetings to improve self-management, and text messages providing health education. Paired t- and chi-square tests were used to determine the significance of the changes in indicators before and after the intervention. Results. Lifestyle behaviors, such as weight and blood pressure monitoring, reduced salt consumption, increased fruit and vegetable consumption, and stress control improved during the intervention (P < 0.001). The EuroQol-Five Dimension Scale showed improvement (P < 0.001) and body mass index, waist circumference, and systolic and diastolic BPs of the participants significantly decreased (P < 0.001). Low-density lipoprotein cholesterol (LDL-C) and triglyceride decreased (P < 0.01) and high-density lipoprotein cholesterol (HDL-C) increased. The estimated glomerular filtration rate (eGFR) increased after the program (P < 0.001). Conclusions. This comprehensive BP control program was effective in improving lifestyle indicators, BP levels, and laboratory results among people living in a low-income urban area of Peru. Increasing opportunities for BP measurement, systematic management of hypertensive patients, and community-based prevention and education programs are paramount to hypertension detection, prevention, and control.